2010
DOI: 10.1158/0008-5472.can-09-4697
|View full text |Cite
|
Sign up to set email alerts
|

STAMP1 Is Both a Proliferative and an Antiapoptotic Factor in Prostate Cancer

Abstract: STAMP1 is predicted to encode a six-transmembrane protein whose expression is highly prostate enriched and is deregulated in prostate cancer. However, the biological role of STAMP1 in prostate cancer cells, or its expression profile at the protein level, is unknown. Here, we find that ectopic expression of STAMP1 significantly increased proliferation of DU145 prostate cancer cells as well as COS-7 cells in vitro; conversely, small interfering RNA-mediated knockdown of STAMP1 expression in LNCaP cells inhibited… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
108
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(123 citation statements)
references
References 39 publications
13
108
2
Order By: Relevance
“…In situ hybridization analysis of 18 normal and 25 tumoral prostate sections showed that STEAP2 expression is about 2.5-fold higher in prostate cancer cells than in normal cells, suggesting that STEAP2 could be implicated in prostate cancer progression (7). Moreover, the immunohistochemical analysis of 17 benign and 67 cancer specimens of prostate tissue was in agreement with mRNA expression data (27). Despite the higher levels of STEAP2 mRNA and protein in prostate cancer, the only study that attempted to establish an association of STEAP2 expression with the Gleason score of prostate tumors was unsuccessful (27).…”
Section: Steap Proteins As Biomarkers Of Diseasesupporting
confidence: 75%
See 2 more Smart Citations
“…In situ hybridization analysis of 18 normal and 25 tumoral prostate sections showed that STEAP2 expression is about 2.5-fold higher in prostate cancer cells than in normal cells, suggesting that STEAP2 could be implicated in prostate cancer progression (7). Moreover, the immunohistochemical analysis of 17 benign and 67 cancer specimens of prostate tissue was in agreement with mRNA expression data (27). Despite the higher levels of STEAP2 mRNA and protein in prostate cancer, the only study that attempted to establish an association of STEAP2 expression with the Gleason score of prostate tumors was unsuccessful (27).…”
Section: Steap Proteins As Biomarkers Of Diseasesupporting
confidence: 75%
“…Moreover, the immunohistochemical analysis of 17 benign and 67 cancer specimens of prostate tissue was in agreement with mRNA expression data (27). Despite the higher levels of STEAP2 mRNA and protein in prostate cancer, the only study that attempted to establish an association of STEAP2 expression with the Gleason score of prostate tumors was unsuccessful (27). However, this question should be further analyzed as the expression of ERK, 1 of the proteins that may mediate the proliferative and antiapoptotic functions of STEAP2, augments from normal to benign prostate hyperplasia and prostate cancer stages (27).…”
Section: Steap Proteins As Biomarkers Of Diseasesupporting
confidence: 74%
See 1 more Smart Citation
“…Apoptosis and the treatments for its induction and detection were as described previously (55). To detect proapoptotic factorinduced apoptosis, cells were treated with 50 ng/mL TRAIL (Enzo Life Sciences), 20 μM LY294002 (Invitrogen), or a combination of both agents for indicated times.…”
Section: Methodsmentioning
confidence: 99%
“…Activation of extracellular signal-regulated kinase (ERK), which has previously been implicated in prostate cancer progression, was reported with ectopic expression of STAMP1 in DU145 cells and, conversely, was strongly down regulated on STAMP1 knockdown in LNCaP cells [7]. Promoter region of the STAMP genes were analyzed and putative presence of tumor suppressor gene p53 and survival gene NFkB response elements were identified and confirmed at the promoter region of STAMP1 and STAMP2 genes [8].…”
Section: Introductionmentioning
confidence: 82%